Desain Penelitian Narrative Research & Grounded Theory - Nabila Azmi Lubis; Yunita Febrianti; Rena Hari Saputri; Lala Indri Artika (Jurnal Zeniusi, 2025)
Qualitative research is an approach that aims to understand social reality, human behavior, and the meaning contained in it through the perspective of the subject under study. In contrast to quantitative research which emphasizes numbers and generalizations, qualitative research prioritizes depth of understanding and interpretation of meaning. In qualitative research, there are various designs that can be used, including Narrative Research and Grounded Theory which are often the main choices for researchers who want to explore complex phenomena. Narrative Research focuses on stories or narratives told by individuals, with the aim of uncovering personal meaning, life experiences, and a person's subjective interpretation of the events they experience. Through this approach, researchers seek to understand how individuals make meaning of their lives, and how these experiences shape their identities and behaviors. Meanwhile, Grounded Theory aims to build theories that are truly born from field data through an inductive approach. Researchers collect data without bringing an initial theory and gradually form categories, concepts, until finally producing a theory that can explain the phenomenon under study. This process involves iterative data collection and analysis through open, axial and selective coding techniques. This article not only discusses the definitions and characteristics of the two designs, but also reviews the types of research, distinctive features, advantages, essential differences, and challenges that may be faced in their application. These challenges include the difficulty in obtaining authentic narratives, the potential for researcher subjectivity, and the complexity of the theory development process. This article is organized through a literature study and descriptive analysis that aims to provide a comprehensive understanding of how and when Narrative Research and Grounded Theory can be appropriately applied in qualitative research.